KARAKTER RUSIP DENGAN PENAMBAHAN KULTUR KERING : Streptococcus sp. - koesoemawardani, Dyah; yuliana, nety (Badan Pengkajian dan Penerapan Teknologi, 2009)
This research aimed to (1) compare the characterization between rusip with Streptococcus sp. and without it, and (2) evaluate chemical, and microbiological. This research done in some steps which was (1) preparation of liquid starter, (2) making of dry starter, (3) application of Streptococcus sp. dry starter to rusip, the water content, level of acidity (pH), total lactic acid bacterial, total fungi, salt content and Nitrogen Volatile Total (NVT) are being monitory. The data were analysed by descriptively. Rusip that fermented for seven days with adding of Streptococcus sp.dry culture produced better pH, total of lactic acid bacterial, salt content, NVT content and also produce higher water content compare with spontaneously fermented rusip. However rusip fermented with adding of Streptococcus sp. dry starter still had weakness that was produce more fungi than spontaneouslyfermented rusip. Characteristic of rusip that fermented with adding of Streptococcus sp. dry starter were : content 57,87% of water, 5,77 pH, 3,98 x 1011 cfu/g of total lactic acid bacterial, 24,64% salt and 51,43 mgN/100g NVT